2022
DOI: 10.1016/j.ejvsvf.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with the New Ovation Alto Stent Graft in Endovascular Abdominal Aortic Aneurysm Repair

Abstract: Introduction Since 2010, the Ovation Abdominal Stent Graft System has offered a new sealing concept, achieved by a sealing ring filled with polymer 13 mm from the renal arteries. In the latest version, called Ovation Alto, the sealing ring is relocated 6 mm closer to the top of the fabric. This study describes the early clinical outcomes, after CE Mark approval in August 2020, of endovascular aneurysm repair with the Alto endograft. Report Eleven patients underwent endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The mean contrast agent volume used was 172 mL, which was similar to that (180 mL) reported by Holden and Lyden [ 6 ]. The results obtained at the 1-month follow-up in a study by de Donato et al [ 9 ] correspond with those obtained in the present study, including a clinical success rate of 100% with no AAA-related mortalities. Type I or III endoleaks, polymer leakage, endograft migration, and sac expansion were not observed.…”
Section: Discussionsupporting
confidence: 91%
“…The mean contrast agent volume used was 172 mL, which was similar to that (180 mL) reported by Holden and Lyden [ 6 ]. The results obtained at the 1-month follow-up in a study by de Donato et al [ 9 ] correspond with those obtained in the present study, including a clinical success rate of 100% with no AAA-related mortalities. Type I or III endoleaks, polymer leakage, endograft migration, and sac expansion were not observed.…”
Section: Discussionsupporting
confidence: 91%
“…A cohort study of 11 patients who underwent EVAR using Alto ( 47 ) reported the device's great potential in early outcomes, as it achieved 100% clinical success (no type I/III endoleak, sac enlargement, stent graft migration, polymer leakage, AAA related mortality, or secondary intervention) at 1- and 6-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Freedom from secondary interventions was 97.3%, while one patient had a type 1A endoleak and received ballooning and bare metal stent placement for intervention on postoperative day 48, which successfully treated the endoleak. Another patient had a device infection and was converted to A cohort study of 11 patients who underwent EVAR using Alto (47) reported the device's great potential in early outcomes, as it achieved 100% clinical success (no type I/III endoleak, sac enlargement, stent graft migration, polymer leakage, AAA related mortality, or secondary intervention) at 1-and 6month follow-up.…”
Section: Altomentioning
confidence: 99%
“…Recently, another initial experience [ 25 ] confirmed the early technical and clinical success of the new Ovation Alto stent graft.…”
Section: Discussionmentioning
confidence: 99%